A COMPARISON OF THE EFFECTIVENESS OF MICRO INFLUENCERS AND KEY OPINION LEADERS THROUGH INFLUENCER BRAND FIT IN BUILDING BRAND TRUST IN GEN Z CONSUMERS ON SOCIAL MEDIA - Indrayani, Rina; Widodasih, R. R. Wening; Pratiwi, Wike (Faculty of Economic and Business, University of Pasundan, 2026)
The rapid growth of social media is transforming digital marketing strategies, particularly in engaging Generation Z (Gen Z) consumers who are highly active and critical of marketing messages. Influencer marketing has become a prominent method through Micro-Influencers and Key Opinion Leaders (KOLs), but the comparative effectiveness in building Brand Trust through Influencer Brand Fit remains insufficiently explained. Therefore, this study aimed to analyze influence of Influencer Brand Fit on Brand Trust and to compare the effectiveness of Micro-Influencers and KOLs among Gen Z consumers in Indonesia. A comparative quantitative method was adopted using experimental content stimuli and a survey of 100 Gen Z Instagram and TikTok users. Data were analyzed using validity and reliability tests, independent sample t-tests, and path analysis. The results showed that Micro-Influencers were more effective in building Brand Trust, with Influencer-Brand Fit acting as a significant mediating mechanism.